Sulphur management in green gram [Vigna radiata (L.) Wilczek] under rainfed condition - Mastkar, Anjni; Kushwaha, H. S. (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif seasons of 2012-13 and 2013-14 on sandy loam soil at Mahatma Gandhi Chitrakoot Gramodaya Vishwavidhyalaya, Chitrakoot, Madhya Pradesh, India to evaluate the performance of greengram for applied sulphur and to work out the appropriate dose of sulphur. Three greengram cultivars viz. PDM 139, Virat, IPM 2 were evaluated under 4 levels of sulphure (0, 10, 20, 30 kg S/ha). Various yield attributes and seed yield of greengram was recorded significantly superior under greengram cultivars PDM 139. While, stover yield was observed significantly higher under cultivar Virat followed by IPM 2. Greengram cultivar PDM 139 produced 36.14% and 13.12% higher seed yield as compared to Virat and IPM 2, respectively. Growth parameters viz. plant height, trifoliates, dry weight/ plant, root length and root dry weight; nodules/ plant, nodules dry weight, yield attributes i.e. pods/plant, pod weight/plant and seeds/pods and seed yield were obtained significantly higher under 30 kg S/ha. Application of sulphur at 30 kg/ha produced 10.73 and 57.65 % higher seed yield and 25.07 and 50.08 % more stover yield over 20 and 0 kg S/ha, respectively. Highest harvest index, net returns and return per rupee was obtained under PDM-139 with 30 kg S/ha. Greengram variety PDM 139 with sulphur @ 30 kg/ha performed better in respect of seed yield and net returns as compared to virat and IPM 2.